2007
DOI: 10.1128/mmbr.00015-07
|View full text |Cite
|
Sign up to set email alerts
|

Function, Structure, and Evolution of the RubisCO-Like Proteins and Their RubisCO Homologs

Abstract: SUMMARY About 30 years have now passed since it was discovered that microbes synthesize RubisCO molecules that differ from the typical plant paradigm. RubisCOs of forms I, II, and III catalyze CO2 fixation reactions, albeit for potentially different physiological purposes, while the RubisCO-like protein (RLP) (form IV RubisCO) has evolved, thus far at least, to catalyze reactions that are important for sulfur metabolism. RubisCO is the major global CO2 fixation catalyst, and RLP is a somewhat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
364
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(375 citation statements)
references
References 78 publications
7
364
1
3
Order By: Relevance
“…indicating their functionality in vivo (Tabita et al, 2007). However, other experiments have shown that type III RuBisCO enzymes are involved in adenosine monophosphate metabolism (Sato et al, 2007).…”
Section: Op5mentioning
confidence: 99%
“…indicating their functionality in vivo (Tabita et al, 2007). However, other experiments have shown that type III RuBisCO enzymes are involved in adenosine monophosphate metabolism (Sato et al, 2007).…”
Section: Op5mentioning
confidence: 99%
“…Trace amounts of RubisCO activity and the lack of phosphoribulokinase activity do not support the operation of the Calvin-Bassham-Benson cycle. Possible functions of the archaeal RubisCO have been discussed (Tabita et al, 2007;Sato et al, 2007;Ashida et al, 2008). P. fumarii is a representative of the family Pyrodictiaceae (Desulfurococcales).…”
Section: Enzyme Activities In P Fumariimentioning
confidence: 99%
“…Form IV is a recently discovered, diverse group of enzymes referred to as Rubisco‐like proteins (RLPs). These enzymes are found within many diverse clades of organisms (including the Proteobacteria, Firmicutes, Chlorobia, Clostridia, Chloroflexi non‐methanogenic euryarchaeota, and the unicellular green alga O. tauri ), lack the active‐site residues of canonically characterized Rubisco, and are not known to carry out the carboxylase/oxygenase activity; the full range of metabolic functions of the RLPs have not been explored but at least some are involved in sulfur metabolism (Singh & Tabita, 2010; Tabita et al., 2007). …”
Section: Introductionmentioning
confidence: 99%